Diagnosis of the Islamic Educational Environment from the Perspective of the Qur'an - Andri Noer Zaelani; Akhmad Alim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Humans cannot stand alone, but are closely related to their environment (ẖabl ma'a biatih), humans cannot be separated from other humans (ẖabl minan nâs), humans also depend on Allah (ẖabl mina Allâh) who is the Almighty, creator and determiner of their lives. The view of the Al-Qur'an which is the basis of the author's argument, is that basically from the womb humans have had several potentials, and the educational environment in the Al-Qur'an is comprehensive and integrated, covers all fields of knowledge, and is oriented towards the world of the afterlife. The educational environment consists of family, madrasah, and community. Families must create an educational atmosphere for their family members, starting from the formation of the ark (future father and mother) to the birth process and formation from childhood to adulthood, so that Islamic Tarbiyah can be implemented and produce educational goals as expected. Schools, historically the existence of schools is a further development of the existence of mosques. This is because the educational process that took place in the mosque in the initial period included educators, students, materials and learning methods that were applied in accordance with the materials and conditions of the students.